The Effect Of Applying the Glenn Doman Method on Homonym Material Toward the Learning Outcomes of 4th Grade Elementary School Students - Adelta, Sherly; Wahid Ibnu Zaman; Zainal Afandi (IJPSE Indonesian Journal of Primary Science Education, 2025)
In Indonesian language learning, there are four language skills that students must master. These four language skills are interconnected and influence one another. Elementary school students need to learn aspects of language, one of which is reading skills. Reading skills themselves have a significant impact on all aspects of students’ activities, especially in learning activities. This research employs an experimental research method with a quantitative approach. The research design used in this experimental study is a Quasi Experimental Design in the form of a Pretest-Posttest Nonequivalent Control Group Design. The sample in this study consists of all fourth-grade students at SDN Ngadi and all fourth-grade students at SDN Kranding, Mojo District, Kediri Regency. Based on the results of data analysis, an asymp. Sig value of 0.002 was obtained, which means that the significance value is smaller than 0.05, thus it can be concluded that there is a difference in learning outcomes between the control class and the experimental class. In addition, the difference can be seen from the average post-test scores obtained by the control class without treatment and the experimental class after treatment. The average post-test score in the control class was 78.7, while the average post-test score in the experimental class was 86.8. From this difference in averages, it can be concluded that the application of the Glenn Doman method in homonym material in the experimental class had an effect on students’ learning outcomes.